2019
DOI: 10.3390/su11041066
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sustainable Human Resource Management in Hospitality: An Empirical Investigation of the Integrated Mediated Moderation Model

Abstract: This research proposed and investigated a mediated moderation research framework that links employee job satisfaction, knowledge sharing, innovation capability, and job performance for sustainable human resource management in hospitality. Data from 395 Taiwanese hospitality companies with structural equation modeling (SEM) analyses, and the results showed that job satisfaction had significantly positive influences on knowledge sharing, both job satisfaction and knowledge sharing were significantly and positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Companies must apply the principles of corporate responsibility to their products, processes and production practices, and this fact requires them to be open to change and innovation. In this situation, SRHRMP can have a positive effect on innovative behaviour [50,75] and, particularly, on employee socially responsible innovative behaviour.…”
Section: The Interdependencies Between Innovative Behavior Innovatiomentioning
confidence: 99%
“…Companies must apply the principles of corporate responsibility to their products, processes and production practices, and this fact requires them to be open to change and innovation. In this situation, SRHRMP can have a positive effect on innovative behaviour [50,75] and, particularly, on employee socially responsible innovative behaviour.…”
Section: The Interdependencies Between Innovative Behavior Innovatiomentioning
confidence: 99%
“…They concluded that, when sustainability is important for the management, employees internalise the sustainability and show greater commitment to adopt a sustainable behaviour. Wang [76] studied a model that matches employees' job satisfaction, knowledge sharing, innovation capability, and job performance for sustainable HRM in hospitality context. With respect to CSR, which is a related subtheme in the sustainable HRM research theme, Lu et al [22] empirically tested the connection between CSR specifically directed toward employees (CSRe) and career development sustainability.…”
Section: Sub-period 2017-2019mentioning
confidence: 99%
“…In the past decades, strategic HRM led organizations to short-term business success [24]. It focused more on financial performance than on other organizational outcomes, ignoring employee's well-being [25].…”
Section: Sustainable Hrmmentioning
confidence: 99%
“…The hospitality industry particularly relies on a high level of interactions between customers and employees. Obtaining and retaining high-quality employees is, thus, a survival strategy for hospitality practitioners to reach a long-term successful business from the perspective of sustainability [24]. Several studies have integrated sustainable HRM into the workplace [28,29], yet few have examined sustainable HRM under a research framework, especially in the hospitality industry, to better comprehend its effects on human work performance.…”
Section: Sustainable Hrmmentioning
confidence: 99%